2021
DOI: 10.1101/2021.07.01.21259656
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proxalutamide Improves Lung Injury in Hospitalized COVID-19 Patients – an Analysis of the Radiological Findings of the Proxa-Rescue AndroCoV Trial

Abstract: Introduction: Antiandrogen are good candidates against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease (COVID-19) due to the inhibition of its entry into host cells by the suppression of TMPRSS2, an enzyme that primes the SARS-CoV-2 spike (S) protein and is key for its cell entry. Proxalutamide is a second-generation nonsteroidal anti-androgen (NSAA) with strong activities on androgen receptor (AR) antagonism, suppression of AR nuclear expression, and downregulation of the membrane-att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…substantial improvements seen in immunological, inflammatory and thrombotic markers with proxalutamide can support reduction of hospitalization [129]. Proxalutamide also significantly improves lung injury in patients with COVID-19 [130]. Cadegiani et al in a double-blind, randomized clinical trial (DB-RCT), investigated the efficacy of proxalutamide 200 mg/day, compared to placebo group regarding viral clearance.…”
Section: Impact Of Drugs That Affect Androgen-mediated Mechanisms In ...mentioning
confidence: 99%
“…substantial improvements seen in immunological, inflammatory and thrombotic markers with proxalutamide can support reduction of hospitalization [129]. Proxalutamide also significantly improves lung injury in patients with COVID-19 [130]. Cadegiani et al in a double-blind, randomized clinical trial (DB-RCT), investigated the efficacy of proxalutamide 200 mg/day, compared to placebo group regarding viral clearance.…”
Section: Impact Of Drugs That Affect Androgen-mediated Mechanisms In ...mentioning
confidence: 99%
“…Since TMPRSS2 is regulated by the androgen receptor, reduction of TMPRSS2 expression by inhibiting the androgen receptor would likely inhibit the entry of SARS‐CoV‐2 into human cells. Proxalutamide is a novel nonsteroidal anti‐androgen with strong antagonism to the androgen receptor 11 . It has been demonstrated to reduce the hospitalization rate in both COVID‐19 male 12 and female 13 outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Proxalutamide is a novel nonsteroidal anti‐androgen with strong antagonism to the androgen receptor. 11 It has been demonstrated to reduce the hospitalization rate in both COVID‐19 male 12 and female 13 outpatients. The final results from the Proxa‐Rescue Trial showed that proxalutamide increased the 14‐day recovery rate by 121% and reduced the 28‐day mortality rate by 78% when compared to the usual care in the treatment of hospitalized COVID‐19 patients.…”
Section: Discussionmentioning
confidence: 99%